2023
DOI: 10.1111/pce.14520
|View full text |Cite
|
Sign up to set email alerts
|

A 14‐3‐3 protein positively regulates rice salt tolerance by stabilizing phospholipase C1

Abstract: The phosphatidylinositol-specific phospholipase Cs (PI-PLCs) catalyze the hydrolysis of phosphatidylinositols, which play crucial roles in signaling transduction during plant development and stress response. However, the regulation of PI-PLC is still poorly understood. A previous study showed that a rice PI-PLC, OsPLC1, was essential to rice salt tolerance. Here, we identified a 14-3-3 protein, OsGF14b, as an interaction partner of OsPLC1. Similar to OsPLC1, OsGF14b also positively regulates rice salt toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Genes encoding PI-PLCs have been found in the genomes of many crop species, including Oryza sativa [ 55 ], Zea mays [ 56 ], Brassica napus [ 57 ], and Glycine max [ 58 ]. We retrieved 22, 9, 13, 5, 5, 7, 6, and 1 protein sequences from Brassica napus , Arabidopsis thaliana , Glycine max , Oryza sativa , Zea mays , Triticum aestivum , Sorghum bicolor , and Solanum tuberosum , respectively ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding PI-PLCs have been found in the genomes of many crop species, including Oryza sativa [ 55 ], Zea mays [ 56 ], Brassica napus [ 57 ], and Glycine max [ 58 ]. We retrieved 22, 9, 13, 5, 5, 7, 6, and 1 protein sequences from Brassica napus , Arabidopsis thaliana , Glycine max , Oryza sativa , Zea mays , Triticum aestivum , Sorghum bicolor , and Solanum tuberosum , respectively ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that 14-3-3 proteins have a significant impact on stress resistance ( Roberts, 2003 ). In rice, OsGF14b improves salt tolerance by interacting with OsPCL1, inhibiting its ubiquitination for protection from degradation, and promoting its activity and stability ( Wang et al., 2023 ). Overexpression of both heterologous PvGF14a and PvGF14g in transgenic Arabidopsis under salt stress reduces seed germination and fresh seedling weight, suggesting the involvement of these genes in the negative regulation of salt tolerance in seedlings ( Li et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , it was found that 14-3-3 proteins can respond to salt stress by regulating the activity of antioxidant enzymes ( Visconti et al., 2019 ; Wang et al., 2019 ). In general, 14-3-3 proteins can interact with many TFs to regulate salt stress resistance in plants ( Chang et al., 2019 ; Wang et al., 2023 ). For example, 14-3-3 proteins can interact with GmMYB173 to regulate antioxidant enzyme activity and hydrogen peroxide scavenging in soybean to regulate salt resistance ( Pi et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent review summarized advances in stress sensing and signalling, functional adaptation, and salinity tolerance breeding (T. Chen et al, 2021), understanding the complexity of salinity tolerance mechanisms in rice is still limited, and real salt‐tolerant rice varieties are not yet available. Wang et al (2023) reported, in this issue, the new functions of a 14‐3‐3 protein, OsGF14b, in regulating stability and function of a previously known protein essential for rice salt tolerance, phospholipase C (OsPLC1), thus improving rice salt tolerance (N. Wang et al, 2023). Although effects of OsDG14b on grain yield and the potential of its incorporation into commercial germplasm were not investigated, this study will stimulate interests in 14‐3‐3 proteins.…”
Section: Abiotic Resilience Of Ricementioning
confidence: 99%